Memaknai Realitas Dunia Maya: Kajian Dramaturgi dalam Film Semu - Zulfikar (UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article attempts to look at the acute phenomenon of the social media generation with its activities and images in cyberspace. The film entitled